1998
DOI: 10.2172/582247
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of fluidic pulse jet mixing for a horizontal waste storage tank

Abstract: STE rThis report has been reproduced directly from the best available copy. .3 .4 . .6 . .8 . .10 . .12 . .14 .15 . .17 . .19 . LIST OF FIGURES 26.Tank W-21 southwest comer after Campaign 4 (BVST-0723-4). . . . . 5 1 27. 28.Tank W-21 southeast comer after Campaign 4 (BVST-0718-4). . . . . 52Tank W-21 east side viewed south after Campaign 4 (BVST-0719 4). 53 29. 30.Tank Ridge National Laboratory ( O N ) . The pulse jet system, consisting of seven modular equipment skids, was installed and commissioned in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Perona et al (1994) studied jet mixing in the horizontal storage tanks at ORNL. Kent et al (1998) demonstrated using PJMs for use in the horizontal storage tanks. and Terrones and Eyler (1993) investigated using submerged liquid jets to mobilize and mix non-Newtonian sludge in horizontal, cylindrical, waste storage tanks (similar to the ORNL Melton Valley Storage Tanks) using the modified time-dependent, finite-volume TEMPEST computer program.…”
Section: Oak Ridge Studiesmentioning
confidence: 99%
“…Perona et al (1994) studied jet mixing in the horizontal storage tanks at ORNL. Kent et al (1998) demonstrated using PJMs for use in the horizontal storage tanks. and Terrones and Eyler (1993) investigated using submerged liquid jets to mobilize and mix non-Newtonian sludge in horizontal, cylindrical, waste storage tanks (similar to the ORNL Melton Valley Storage Tanks) using the modified time-dependent, finite-volume TEMPEST computer program.…”
Section: Oak Ridge Studiesmentioning
confidence: 99%
“…al. 6 The existing Moyno pumps would be used to transfer the waste from the BVESTs to the MVSTs. This option is anticipated to require the use of additional tanks for conditioning and storage of the wastes retrieved from W-9 before these wastes are transferred to the BVESTs and to supply recycled supernate.…”
Section: Tank Waste-retrieval System To Transfer Waste From W-9 To Thmentioning
confidence: 99%